Genetic alterations in streptomycin-resistant Mycobacterium tuberculosis: mapping of mutations conferring resistance. - Meier, A (1994)
We report on the identification of mutations associated with streptomycin resistance in Mycobacterium tuberculosis. Two isolates (3656 and 3976) showed a wild-type ribosomal protein, S12, but exhibited a single point mutation at 16S rRNA position 491 (C-->T) or 512 (C-->T), respectively. Sequence analysis of a third isolate (2438) revealed a single base change at 16S rRNA position 904 (A-->G). This position is equivalent to invariant position 913 of the Escherichia coli 16S rRNA gene, an A-->G transition of which has been shown previously to impair streptomycin binding and streptomycin-induced misreading in vivo. Surprisingly, strain 2438 harbors an additional mutation in the ribosomal protein S12 (Lys-88-->Gln).